Intravenous access in patients with morbid obesity - Latos, Maciej; Szymczak, Artur; Solecki, Marceli (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2024)
Intravenous therapy is a common procedure performed in hospitals. Patients in surgical departments usually require intravenous access due to a planned surgical procedure, and therefore anaesthesia, pain, antibiotic, and fluid therapy. Problems in obtaining intravenous access, even by experienced clinicians, can be caused by difficult intravenous access (DIVA). One risk factor for DIVA is obesity. The purpose of this paper is to present a case report of a patient with DIVA due to morbid obesity, who was scheduled for clean diabetic feet associated with type 1 diabetes. A case study method was used in this study. By implementing the appropriate strategy, the patient’s comfort was increased, staff time was saved, and the planned therapy was successfully carried out. Vascular access teams consisting of experienced providers should be present in every hospital to deliver the highest quality medical services according to patients’ needs.